2017
DOI: 10.1352/1944-7558-122.3.215
|View full text |Cite
|
Sign up to set email alerts
|

The Arizona Cognitive Test Battery for Down Syndrome: Test-Retest Reliability and Practice Effects

Abstract: A multisite study investigated the test-retest reliability and practice effects of a battery of assessments to measure neurocognitive function in individuals with Down syndrome (DS). The study aimed to establish the appropriateness of these measures as potential endpoints for clinical trials. Neurocognitive tasks and parent report measures comprising the Arizona Cognitive Test Battery (ACTB) were administered to 54 young participants with DS (7–20 years of age) with mild to moderate levels of intellectual disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 40 publications
1
53
0
Order By: Relevance
“…Interestingly, there is evidence from other treatment studies and measure evaluation studies involving individuals with intellectual disabilities that many widely used measures also have high "failure rates" in this range. In a measure evaluation study conducted by Edgin et al [74], for example, approximately one-third of 7-to 20-year-olds with Down syndrome were at the floor on the CANTAB Spatial Span subtest because of either noncompliance or an inability to achieve a sufficient number of correct responses. Similarly, Hessl et al [22] administered the NIH Toolbox Cognitive Battery, which was normed on children with TD as young as 3 years, to 6-to 25-yearolds with ID.…”
Section: Psychometric Findings For the Full Samplementioning
confidence: 99%
“…Interestingly, there is evidence from other treatment studies and measure evaluation studies involving individuals with intellectual disabilities that many widely used measures also have high "failure rates" in this range. In a measure evaluation study conducted by Edgin et al [74], for example, approximately one-third of 7-to 20-year-olds with Down syndrome were at the floor on the CANTAB Spatial Span subtest because of either noncompliance or an inability to achieve a sufficient number of correct responses. Similarly, Hessl et al [22] administered the NIH Toolbox Cognitive Battery, which was normed on children with TD as young as 3 years, to 6-to 25-yearolds with ID.…”
Section: Psychometric Findings For the Full Samplementioning
confidence: 99%
“…Although dated, the SIB‐R is the recommended measure in studies of cognition among individuals with DS (Edgin et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Existing measures often lack reliability, can be insensitive to change among individuals with Down syndrome, and may not be suitable for repeated assessment (See Edgin et al, 2017;Esbensen et al, 2017, & Keeling et al, 2017 for overviews). Esbensen et al (2017) suggested that the BRIEF (parent/caregiver report measure) has adequate test-retest reliability among individuals with Down syndrome (see also D' Ardhuy et al, 2015).…”
Section: Existing Executive Function Tasks Used With Adults With Downmentioning
confidence: 99%